RISK FACTORS ASSOCIATED WITH DIABETIC FOOT ULCERS IN PATIENTS WITH TYPE 2 DIABETES MELLITUS (Asian Journal of Medical Research and Health Sciences, 2026)
Introduction: Type 2 Diabetes Mellitus (T2DM) is a chronic metabolic disorder characterized by persistent hyperglycemia, which leads to long-term microvascular and macrovascular complications. Among these, diabetic foot ulcer (DFU) is one of the most debilitating complications, significantly contributing to morbidity, reduced quality of life, prolonged hospital stay, and non-traumatic lower limb amputations. DFU develops due to a combination of peripheral neuropathy, peripheral arterial disease, and minor foot trauma, often aggravated by poor glycemic control and inadequate foot care practices. Identification of modifiable and non-modifiable risk factors is essential for early prevention and effective management. This study aims to evaluate the risk factors associated with diabetic foot ulcers in patients with Type 2 Diabetes Mellitus. Aims: To identify and analyze the risk factors associated with the development of diabetic foot ulcers in patients with Type 2 Diabetes Mellitus. Materials and methods: This was a hospital-based observational study conducted in the Department of Medicine, Malti Multispecialty Hospital and Medical College, Turkhed, Taluka Murtizapur, District Akola, Maharashtra, India, over a period of one year. The study population comprised patients diagnosed with Type 2 Diabetes Mellitus attending both outpatient and inpatient departments. A total sample size of 100 patients was included in the study to evaluate the risk factors associated with diabetic foot ulcers among these patients. Results: The present study included a total of 100 patients with Type 2 Diabetes Mellitus, of whom 40 patients had peripheral arterial disease (PAD) and 60 patients did not have PAD. The analysis showed a significant association between PAD and diabetic foot ulcer (DFU). Among the 40 patients with PAD, 25 patients (62.5%) developed DFU, while 15 patients (37.5%) did not develop DFU. In contrast, among the 60 patients without PAD, 15 patients (25.0%) developed DFU and 45 patients (75.0%) remained free of ulcers. Statistical analysis revealed that the association between PAD and DFU was significant (p = 0.003) . Conclusion: Diabetic foot ulcer in Type 2 Diabetes Mellitus is a multifactorial complication influenced by both modifiable and non-modifiable risk factors. Early identification of high-risk patients through regular screening for neuropathy and vascular disease, along with strict glycemic control and patient education on foot care, can significantly reduce the incidence of diabetic foot ulcers. A multidisciplinary approach is essential for effective prevention and management, ultimately reducing the burden of disability and amputation.